Revision of Microtoena (Lamiaceae) in Java, Indonesia - Santoso, Heri; Felayati, Themas; Sudarmono (Phytotaxa, 2026)
Microtoena in Java is formally here revised, yielding a single new species, i.e., M. javensis. The new species, long known as M. insuavis, is clearly distinct by a set of morphological characters, including stem indumentum, calyx length, calyx mouth shape, cyme branching, style lobe shape, and inflorescence indumentum. Description, color photographs, phenology, and conservation status for this new species are also presented. This study clarifies that M. javensis is the only Microtoena species in Indonesia that occurs in the southern hemisphere.